Tuning the properties of all natural polymeric scaffolds for tendon repair with cellulose microfibers - Diaz, Florencia; Zimmermann, Lars; Dale, Tina P.; Forsyth, Nicholas R.; Boccaccini, Aldo R. (Carbohydrate Polymer Technologies and Applications, 2024)
Rotator cuff injuries affect a large percentage of the population worldwide. Surgical repair has rates of failure of up to 70%, and existing materials used in the reinforcement of injuries often lack appropriate mechanical properties and biodegradability. There is a clinical need for tendon biomaterials that enable cell attachment and proliferation, while supporting mechanically the injury site. In this work, we develop a novel all-natural polymeric scaffold for applications in the supraspinatus tendon of the shoulder. The unidirectional freezing technique is applied to a chitosan-gelatine matrix containing varying cellulose concentrations, followed by crosslinking with genipin. The viability of the technique using a custom 3D printed mould is evaluated. The scaffolds' morphology and mechanical properties are extensively characterized: the ultimate tensile strength of the material with 20% cellulose was found to increase 6-fold compared to scaffolds without cellulose; significant effects on the microstructure of the scaffold were evidenced via scanning electron microscopy. Furthermore, the biocompatibility of the materials was characterized with both porcine tendon derived cells and normal human dermal fibroblasts. All scaffolds are highly biocompatible, the incorporation of cellulose results in higher cell metabolic activity values and density of cells on the surface of the material. Scaffolds containing 20% cellulose fibers were found to possess the optimal biomechanical properties for applications in rotator cuff tendon repair.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Aligned ice templating; Biomaterials; Polymeric scaffolds; Tendon tissue engineering